Wandering Chapel Choirs of the Dniprosoyuz: Importance for the Present from the Perspective of Historical Retrospect - Zasadna, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the study is to study the little-known pages of Ukrainian choral art. For a long time, all that was associated with the period of Ukrainian statehood, as well as the Ukrainian liberation struggles of the 20s of the 20th century against the bolsheviks, was held "by seven castles". After the independence of Ukraine in 1991, the archives of this period gradually began to open, and researchers as well as the public discovered that this period was marked by an extraordinary rise in all spheres of national life: science, art, education, linguistics, religion, etc. This “explosion” was not a spontaneous phenomenon, but rather a culmination of those processes that preceded it. The creation of national choral chapters, as well, was a result of the powerful choral movement of the early twentieth century. After the revolution of 1917, the young Ukrainian state had the opportunity to declare itself to the world, as well as to know oneself, to prove to itself its unique national identity. And in this sense, two fateful decisions were made: the formation of two choir chapels — the Republican, headed by O. Koshits for an artistic representative mission abroad, and — a chorus on the basis of the Dniprosoyuz, according to the original plan of the traveling model choir, the example of which would be local Choirs in various cooperatives and other organizations and societies. Thus, the Ukrainian choir became an important strategic element of both the foreign and the national cultural policy of the state. The scientific novelty is determined by its focus on in-depth study of the history of the creation of the outstanding Ukrainian team of the NZAK of Ukraine “Dumka”, namely the period of its foundation and its first trips as the State Traveling Chapel Choir, which made it possible to substantially complement knowledge about the progress of the choral movement in Ukraine of the 20s of the twentieth century. The main objective of the study is to identify the main principles of the creation of the Wandering Chapel Choirs in Ukraine, as well as to substantiate their role in the development of Ukrainian choral art and meaning for enlightening and raising the national consciousness of both the mentioned period and the present. The article uses methodology of research, in particular, historical, system-analytical, cultural, realized with the help of historical-retrospective functional approach. With the help of which it became possible to highlight the history of the creation of Ukrainian wandering chapel choirs, their artistic and educational mission, realization, and perception of different layers of the population. As a result, an analysis of a certain public "cut" of the audience attending concerts of the chapel choirs was carried out to realize the degree of artistic influence and the ability to transform the national consciousness. Thus, according to the results of the study, the extraordinary significance of the specific choral art for the education and development of Ukrainian society was revealed.